Pertanggungjawaban Debitur yang Melakukan Wanprestasi dalam Kontrak Bisnis - Raditya Alief Aqshal Tabina; Anang Dony Irawan (Pagaruyuang Law Journal, 2026)
Law is always used as the foundation in all life activities, particularly law in contractual agreements. Law in contractual agreements regulates everything related to agreements between two or more parties, which means mutually binding. The main legal basis in Indonesia is the Civil Code (KUH Perdata) Article 1338. Contract Law serves as the foundation in various transactions, both in daily life and when running a business. By understanding Contract Law, we can protect our rights and interests, in order to avoid the possibility of default occurring. Default (wanprestasi) is a situation where one party in an agreement does not fulfill their obligations. This can occur due to various reasons, such as negligence, intentionality, or obstacles beyond that party's control. Default is regulated in the Civil Code (KUH Perdata) Articles 1238 and 1243. The type of research used is normative juridical, using statutory regulations or related regulations to analyze a legal issue so that the resolution of a legal conflict can be resolved based on applicable laws while paying attention to the substance and hierarchy of regulations or laws. This research aims to identify several forms of legal liability that can be imposed on perpetrators of default in business contracts. By examining various cases and relevant statutory regulations.